Improvement of the catalytic performance of a Bispora antennata cellulase by replacing the N-terminal semi-barrel structure. (October 2016) - Zheng, Fei; Huang, Huoqing; Wang, Xiaoyu; Tu, Tao; Liu, Qiong; Meng, Kun; Wang, Yuan; Su, Xiaoyun; Xie, Xiangming; Luo, Huiying
Highlights: An acidic mesophilic cellulase of GH5 ( Ba Cel5) was identified in B. antennata . Effect of N-terminal barrel structures on its catalytic performance was studied. Replacing the N-terminal (βα)3 or (βα)4 barrel with that of Te Egl5A improved the specific activity up to 6.7-fold. Barrel structure replacement also improved the catalytic efficiency up to 4.7-fold. N-terminal replacement introduced more hydrogen bonds and enlarged catalytic cavity. Abstract: The aim of this work was to study the contribution of the N-terminal structure to cellulase catalytic performance. A wild-type cellulase ( Ba Cel5) of glycosyl hydrolase (GH) family 5 from Bispora antennata and two hybrid enzymes ( Ba Cel5 127 and Ba Cel5 167 ) with replacement of the N-terminal (βα)3 (127 residues) or (βα)4 (167 residues)-barrel with the corresponding sequences of Te Egl5A from Talaromyces emersonii were produced in Pichia pastoris and biochemically characterized. Ba Cel5 exhibited optimal activity at pH 5.0 and 50 °C but had low catalytic efficiency (25.4 ± 0.8 mL s −1 mg −1 ). In contrast, Ba Cel5 127 and Ba Cel5 167 showed similar enzymatic properties but improved catalytic performance. When using CMC-Na, barley β-glucan, lichenan, and cellooligosaccharides as substrates, Ba Cel5 127 and Ba Cel5 167 had increased specific activities and catalytic efficiencies by ∼1.8−6.7-fold and ∼1.0−4.7-fold, respectively. The catalytic efficiency of Ba Cel5 167 was even higher than that of parental proteins. The underlying mechanism was analyzed by molecular docking and molecular dynamic simulation.